Does Menzerath–Altmann Law Hold True for Translational Language: Evidence from Translated English Literary Texts. Issue 1 (2nd January 2022) - Jiang, Yue; Ma, Ruimin
ABSTRACT: Menzerath–Altmann Law (MAL) is regarded as one of the fundamental laws of language due to its extensive validity for different languages at various linguistic levels and applicability for register differentiation. However, whether MAL holds true for translational language remains to be answered. Translational language, different from both the source language and target original (non-translated) language, is viewed as 'the third code'. This study delves into the validity of MAL for translated English literary texts and its comparable original texts by exploring the relationship between the sentence length (in number of clauses) and the clause length (in number of words). Results of the study corroborate that MAL held true for both original and translated texts. In addition, both a and b, the fitting parameters of MAL formula, could differentiate the translational language from the original, thus justifying the uniqueness of translational language as 'the third code' in its own right. This finding suggests that the fitting parameters might be viable indicators for typological differentiation in translation studies. Further, exploring the dynamic relations between a language construct and its constituents may shed some light on the translating process.